COFFEE PRIANGAN IN THE NINETEENTH CENTURY - Zakaria, Mumuh Muhsin (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2009)
The course of Priangan history during almost two centuries, in the VOC and Dutch colonial period, was nearly identical to coffee cultivation. The consideration based on that Priangan was temporally the first region in Java where coffee cultivation introduced; then quantitatively coffee cultivation of Priangan engaged the number of manpower and large of land extensively so that consequently the product of coffee from this residency was always the highest than the other residencies throughout Java. Besides, in favour of coffee cultivation, within residency was operated very long aged system then known as Preangerstelsel from 1677 until 1870. (de Klein: 1986: 34)